PERNIKAHAN DAN HIKMAHNYA PERSPEKTIF HUKUM ISLAM - Ahmad Atabik; Khoridatul Mudhiiah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
In essence, marriage is a religious order that is governed by Islamic law and is the only authoritative sexual relations in Islam. As rahmatan lil ‘alamin, Islam has determined that the only way to meet the biological needs of individuals living just by marriage, marriage is one thing that is very interesting if we look more closely at the content of the meaning of this marriage problem. The Qur’an has explained that among the purpose of marriage is to find peace in one’s life both for men and women (litaskunu ilaiha). Islam ordained marriage as a vehicle of family to achieve happiness in life. Therefore, in this article, the author explores the notion of marriage, the legal basis, as well as the terms and harmonious marriage’s wisdom that prescribed.Keywords: marriage, Saqinah, law and Islam